Sterlite Technologies Limited (STL) : from cables to solution selling - Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2020)
On April 21, 2020, Manish Sinha, Chief Marketing Officer at Sterlite Technologies Limited (STL) was busy working at his computer. Bang in the middle of the COVID -induced lockdown, he had just received an email from an account manager regarding many customers enquiring about increasing the capacity of their data network. COVID-19 had led to a growth in data network usage. He had also come to know that global leaders had started accelerating investment in virtualiszed infrastructure, for example, telecom operators started driving fiber network creation, cloud companies, enterprises, and governments started creating large -scale networks for data centres and so on. These network investments were driven by the need to connect everyone with high -quality broadband.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sales Management -- Case studies; Strategic planning -- Case studies; Pricing -- Case studies